Perceived sources of stress and anxiety among Senegalese dental students - Lecor, Papa A.; Gadiaga, Rokhaya; Dieng, Seynabou; Soumboundou, Sankoung (International Journal of Research in Medical Sciences, 2023)
Background: Dental studies are stressful and anxiety-provoking. The aim of this study was to assess the stress and anxiety levels of dental students at Cheikh Anta Diop university in Dakar, Senegal. Methods: A descriptive cross-sectional study was conducted among 133 students. A general stress self-questionnaire (Perceived stress scale 14), another specific to dentistry studies and a final Spielberger anxiety questionnaire were distributed manually or electronically to students regularly enrolled in master’s 1 and 2 at the institute of odontology and stomatology of Cheikh Anta Diop university in Dakar. Results: A total of 121 students responded, giving a response rate of 90.97%. The average stress level was 20.8±1.08. Of these, 14 students (11.6%) had mild stress, 75.2% had moderate stress and 13.2% had high stress. The most commonly reported stress factors specific to dentistry studies were examinations and ongoing tests (67.7%), the pre-clinical transition to the clinic (70.3%), patient delays or missed appointments (83.5%), fear of making mistakes (67%, i.e., perforation, medical contraindications, etc.), the availability of equipment (70.3%), and conservative odontology and endodontics procedures (71.6%). Concerning anxiety, 113 students (93.4%) had a moderate level of anxiety and 2 students (1.6%) had a high level of anxiety. Conclusions: This study showed that stress and anxiety are frequently found among dental students. Intervention strategies based on raising awareness and promoting psychological well-being in the educational context should be adopted for these students.